Comparative Analysis of Business Model Innovation in Indonesian Records Label. Case: Trinity Optima Production and Music Factory Indonesia - Mayola, Shavira; Dellyana, Dina (Journal of Business and Management, 2015)
Abstract - In the past few years, records label was facing changes in the music industry that includes opportunities and threat. The opportunities are the rise of digital music that brings out several new product formats, also the partnership with partners to create new platform. Records label also faced the piracy issue as the main threat, which caused great loses to their profit. Therefore, records label, especially in Indonesia, needs innovation in their business model to overcome those changes in music industry structure.This research used the qualitative data research method by using semi-structured interview and secondary data. The respondents in the interview were the member of Trinity Oprima Production and Music Factory Indonesia, especially the business development and digital team. This research revealed the business model canvas, the innovation process and the result of business model innovation implementation. The innovation process shows that both company have initial and existing innovation that have different phases. They was succeed as shown from the result that is measured from the sales unit, margin, and complexity of innovation. By the result of this research, both companies are suggested to have a deep understanding of their business model and make a mapping for the company and partner potential and capability with also evaluate the readiness of the market to accept innovations. Records label also suggested to apply the 360 degrees business model, adaptive to changes and communicate with the partners to create innovations. For the distributors in general, they should apply the super-distribution strategy to gain maximum benefit and be able to expand their distribution channel in form of digital sales or innovation.Â Keywords: Business Model Innovation, Indonesian Records Label, Music Industry, Music Business Model.